Follicular somatic cell factors and follicle development - Buratini, J. [UNESP]; Price, C. A. (CSIRO Publishing, 2011)
Considerable attention is currently paid to oocyte-derived secreted factors that act upon cumulus and granulosa cells. Also important for follicle development are somatic cell-derived secreted factors. This is illustrated by the ability of granulosa cell-derived Kit ligand (KITL) to promote primordial follicle activation, and the loss of follicle development that accompanies KITL gene disruption. This review summarises our current understanding of somatic cell factors during both preantral and antral follicle growth, involving not only signalling from granulosa cells to the oocyte, but also signalling between granulosa and theca cells. Principal granulosa cell-derived factors include activin, anti-Mullerian hormone (AMH), bone morphogenetic proteins (BMPs) and fibroblast growth factors (FGFs). Theca cells also secrete BMPs and FGFs. The interplay between these factors is equally important for follicle growth as the activity of oocyte-derived factors.
Keywords: BMP; FGF; folliculogenesis; granulosa cells; intra-ovarian factors; theca cells